«A Muvra», 1920-1939: la caricatura in Corsica - Marie-Claude Lepeltier è nata nel 1962 nella regione della Basse-Normandie. Giunta in Corsica, ha ripreso i suoi studi storia conseguendo la laurea nel 1997. Attualmente è bibliotecaria dell’Université Pascal Paoli di Corté. Responsabile del fondo regionale, lavora all’attuazione di un “piano di conservazione condivisa dei periodici corsi” in collaborazione con le biblioteche pubbliche e gli Archivi dipartimentali dell’isola. (Diacronie. Studi di Storia Contemporanea, 2014)
At the end of XIX century nationalist movements proliferated all over Europe. During this period, an autonomist tendency emerged in Corsica. In 1923, Petru Rocca, inspired by the Sardinian Action Party, founded Partitu Corsu d’Azione which subsequently took the name of Partitu Corsu Autonomista. This party, arisen in the inner circle of intellectuals, denounced that French political system was the cause of all of the island problems and defended Corsica’s language and culture. The political newspaper «A Muvra», founded in 1920 – and partly edited in Corsican language – served as tribune of the PCA, fighting against Corsica’s “Frenchification”.